ONLINE BANK PAYMENT POINT (PPOB) INNOVATION TO EASE PAYMENT OF LAND AND BUILDING TAX (PBB) THROUGH BUMDES - Kurniawati, Erna; Agustina, Isna Fitria (Journal of Geography, Regional Planning and Development, 2024)
General Background: This research discusses innovations in public service delivery, specifically focusing on the role of BUMDes (Village-Owned Enterprises) in facilitating Land and Building Tax (PBB) payments. Specific Background: The implementation of the Online Bank Payment Point (PPOB) system in BUMDes Karya Sejahtera, Kemantren Village, addresses society’s increasing need for fast and efficient transaction methods. Knowledge Gap: While the PPOB system has been applied in various areas, its role and impact in rural tax payments through BUMDes remain underexplored, particularly in enhancing service efficiency and accessibility. Aims: This study aims to analyze how PPOB innovations through BUMDes ease tax payments and support community needs. Results: Using a descriptive qualitative method with purposive sampling and data analysis by Miles and Huberman, the research identifies PPOB innovations aligning with Rogers’ innovation theory indicators: (1) Relative Advantage – BUMDes benefits financially and updates data in real time, (2) Compatibility – addresses societal needs for fast and easy transactions, (3) Complexity – PPOB is easy to access and operate, (4) Trialability – the system’s benefits are proven and accepted, and (5) Observability – the innovation's effectiveness is visible. Novelty: This study highlights how PPOB services create tangible benefits, allowing timely and efficient tax payments while supporting real-time financial data management. Implications: The implementation of PPOB innovations strengthens BUMDes' role in enhancing public service efficiency and encourages further development of payment services to meet community needs.